Формування кредиту довіри до публічної особистості - Нєнов, І. Г.; Ненов, И. Г.; Nenov, I. (My University, 2010)
This article discusses the basic requirements for public statements of politicians, government officials of various levels, whose dialogue with society became a factor control. That what prevents a public personality to gain the audience's credibility, how to overcome the ten errors of public people is described in this article on the basis of experience gained by orators, statesmen of Ancient Greece and Rome and sociological studies.
Нєнов І. Г. Формування кредиту довіри до публічної особистості / І. Г. Нєнов // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С.309-317.
Keywords: формування кредиту довіри до публічної особистості; вимоги до публічних виступів політиків, державних керівників різних рівней; кредит довіри до публічної особистості; формирование кредита доверия публичным личностям; требования к публичным выступлениям политиков, государственных руководителей разных уровней; кредит доверия публичным личностям; the formation of public personalities credibility; requirements for public statements of politicians, government leaders at various levels; the credibility of public personalities